The explosive power generation capacity in Japanese internationally competitive sprint and all-round speed skaters - Kumagawa, D.; Akiyama, K.; Imawaka, T.; Arimitsu, T. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Explosive power is considered an important factor in speed skating short distance events. Because the force and power generation capacities of the lower limb muscles are improved by speed skating training in speed skaters (Nemoto et al. 1990, de Koning et al. 1991). On the other hand, there is little knowledge about the difference between senior athletes and junior skaters regarding explosive power generation capacity among top skaters. This study therefore evaluated the maximal power generation capacity of senior and junior Japanese internationally competitive speed skaters. METHODS: Participants were Japanese male and female senior and junior speed skaters. They were divided into two groups according to age category: senior skaters (SS; 19 years old and over) and junior skaters (JS; 18 years old or younger). In addition, these participants were divided according to their skating event into two groups of sprinters (SP) and all-round skaters (AR) for both males and females. Their jumping ability was tested in squat jump, countermovement jump with arm swing and without arm swing. Subsequently, participants performed a 30-second all-out Wingate cycling test to measure peak and average power. RESULTS: Regarding the three types of jump heights, SP skaters of both JS, SS, and male and female showed significantly higher values than AL skaters. Peak power in the Wingate cycling test was significantly higher for SP skaters than for AL skaters in both JS and SS. SP skaters showed higher average power than AL skaters in JS and SS for males and SS for females. In addition, peak and average power for both SP and AL skaters, SS showed significantly higher values than JS. Additionally, there was a significant difference in relative power per body weight between JS and SS. CONCLUSION: These results indicate that the ability to produce explosive power may be further improved not only in sprint skaters but also in all-around skaters from the junior stage onwards.